Applicable law in investor-state arbitration : the interplay between national and international law - Kjos, Hege Elisabeth (Oxford : Oxford University Press, 2013)
Investment arbitration has become the key forum to settle disputes between investors and the host state. It is not clear from the arbitration agreements which body of law the arbitrators should apply: national or international. This book examines how the legal framework which the arbitral panels operate in influences which body of law they apply.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed on Apr. 5, 2013).
Keywords: Investments, Foreign (International law); Arbitration and award; International commercial arbitration; Investments, Foreign -- Law and legislation